The concepts of sympathy and humanitarianism in the moral philosophy of David Hume - Gelvez, Carlos Ruben; Rojas Claros, Armando (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In this paper, we analyze Humes’s principles of sympathyand humanitarianismin both the Treatise of human natureand An Inquiry concerning the principles of morals, in order to establish whether Hume made ​​a change of principle between these two works, which significantly alter his moral theory. All this on the understanding that sympathy requires a theoretical framework for justification and correction of selfish feelings that humanitarianism, which appeal to politically correct feelings, completely abandon.